The impact of an anaesthetic protocol on blood and renal acid-base parameters during a study of ECF volume expansion in a small group of clinically healthy rats - Walsh, P. A.; Donovan, D.J. O’ (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The purpose of this study was to assess the suitability of an anaesthetic protocol for the investigation of blood and urinary acid – base parameters in a group of clinically healthy rats. Six rats were lightly anaesthetized with di-ethyl ether. Intraperitoneal injections of sodium pentobarbitone were given to maintain the anaesthesia. A solution containing 0.9% saline and 3% ethanol was infused at a rate of 87µl.min-1 via an indwelling cannula, which had been placed in the jugular vein. Arterial blood samples were collected from the carotid artery towards the termination of the infusion period. ABG analysis gave the following data: pH = 7.26 ± 0.04 (n=6), pCO2 = 56 ± 4 mmHg (n=6), and [HCO3] = 24 ± 3 mmoles.Litre-1 (n=6). Urine was collected at timed intervals from the left kidney through a cannula, which had been positioned in the ureter. Urinary specimens were analysed for flow rate and ammonium concentrations. Very low urinary flow rates were observed, which did not increase significantly over the course of the time frame of the infusion. However, urinary ammonium increased significantly from 4.59 ± 2.70 to a maximum excretion rate of 15.21 ± 12.94 µmoles.hr-1 (n=6), p< 0.05. Considering the development of hypercapnia, respiratory acidosis, and increased urinary ammonium excretion during the course of the study, the anaesthetic regimen that was used was deemed to be an unsuitable modality for the study of either respiratory or renal function in the rat.